Evidence-based medicine measures for neural monitoring in thyroid surgery - Zanghì, Guido Nicola; Sun, Hui; Dionigi, Gianlorenzo (Annals of Thyroid; Vol 3 (April 2018): Annals of Thyroid, 2018)
Intraoperative neural monitoring (IONM) in thyroid and parathyroid surgery is not based on class I evidence. IONM in thyroid surgery is currently limited to class II and III studies (1-7).